Modelling Sustainable Entrepreneurship in The Covid-19 Era - Bustos-Aguayo, José Maros; Bermúdez-Ruíz, Gilberto; Juarez-Najera, Margarita; Espinoza-Morales, Francisco; García-Lirios, Cruz; Carreón-Guillén, Javier; Hernandez-Valdes, Jorge; Sandoval-Vazquez, Francisco Ruben (Journal of Social Transformation and Regional Development, 2021)
Anthropocentrism and ecoperiphery are two foundations that the present work used to specify a model for the study of sustainable local entrepreneurship. The differences between beliefs of scarcity and abundance of resources generate values, skills and knowledge that guide the undertaking of conservation or consumption of natural resources. A review of the Human Development problem, the theoretical and conceptual frameworks, as well as the most recent findings about social entrepreneurship allowed the specification of the relationships between the factors reviewed for discussion. Given that the documentary research allowed the discussion of two options for social entrepreneurship, one oriented to the conservation of nature and the other oriented to the exploitation of natural resources and the consumerism of public services, it was possible to anticipate study scenarios in those that the analysis of local and sustainable would start with perceptions, beliefs, values, knowledge and skills that make it possible to explain austere or consumerist lifestyles. The objective of this work was to specify a model for the study of sustainable entrepreneurship considering a review of the literature from 2019 to 2021. A cross-sectional and psychometric work was carried out with a sample of 450 coffee growers. A structure of three factors was found that explained 27% of the total variance, although the contrast of the model is recommended in other scenarios and samples.